Recurrence and Risk Factors of Giant Cell Tumors in Hand Bones: A Systematic Review - Ori Berger, MD; Mor Mendelson, BSc; David Goren, MD; Andrey Andrakhanov, MD; Ran Talisman, MD (Plastic and Reconstructive Surgery, Global Open)
Background:. Giant cell tumor of bone (GCTB) is a locally aggressive tumor that may affect the bones of the hand and rarely causes pulmonary metastasis. It exhibits a variable recurrence rate after surgical interventions, which presents challenges in its management. This systematic review aims to delineate recurrence rates and identify risk factors for GCTB in the hand. Methods:. We conducted a systematic literature search in April 2024, following PRISMA guidelines, on PubMed and TDNet for studies reporting postsurgical recurrence of GCTB in the hand. Cohort and case-control studies provided recurrence rates, whereas case reports and series were utilized to identify risk factors, compensating for the sparse data in the primary studies. We used descriptive statistics, χ2 tests, and logistic regression to analyze demographics, lesion characteristics, treatments, and outcomes. Results:. We reviewed 13 cohort and case-control studies involving 244 patients, finding an overall recurrence rate of 19.57%. Curettage was associated with higher recurrence rates compared with other surgical methods. After additional review of case reports, a limited range of motion in patients emerged as a significant protective factor against recurrence, suggesting potential benefits in surgical management and outcome prediction. Conclusions:. The significant recurrence rate associated with curettage highlights the need for alternative surgical strategies in GCTB management of the hand. The protective role of limited ROM underscores the importance of thorough preoperative assessments to optimize surgical approaches and enhance patient outcomes.